English Pronunciation Among Fataluku Speakers: Consonants and Vowels in Focus - Muntasir, Muntasir; Rahman, Fadhlur; A’la, Putri Nurul; Azmy, Khairul; Siregar, Try Mahendra (JETLEE : Journal of English Language Teaching, Linguistics, and Literature, 2025)
This study investigates the challenges faced by native Fataluku speakers in learning English pronunciation and the potential confusion experienced by native English speakers when interacting with Fataluku speakers who are currently learning English. These challenges arise due to phonetic differences between the two languages which can affect the effectiveness of cross-language communication. This study used voice recordings from native Fataluku speakers and analyzed consonant and vowel sounds by applying the Perceptual Assimilation Model (PAM). This model allows the identification of phonetic similarities and differences between Fataluku and English sounds, as well as the prediction of potential difficulties in second language sound acquisition.The results show that Fataluku speakers face significant difficulties in pronouncing some English sounds. The main difficulties are found in consonant pairs such as /ŋ/ and /n/, which are often mispronounced or not consistently realized. In addition, vowel pairs such as /ɪ/ and /ʊ/ are also challenging, mainly due to the absence of similar sounds in Fataluku. These findings highlight the difficulties in pronunciation not only affect Fataluku learners' confidence in speaking English, but can also lead to misunderstandings in cross-cultural interactions. As a result, cross-language communication becomes less effective, potentially affecting social integration, educational and employment opportunities for Fataluku speakers. Therefore, these findings have important implications for language teaching practices, including the need for teaching strategies that focus on difficult sounds and a contrastive phonetic approach to help Fataluku speakers improve their English speaking skills.